Γδ T‐cell responses during HIV infection and antiretroviral therapy. Issue 7 (17th July 2019) - Juno, Jennifer A; Eriksson, Emily M
Abstract: HIV infection is associated with a rapid and sustained inversion of the Vδ1:Vδ2 T‐cell ratio in peripheral blood. Studies of antiretroviral therapy (ART)‐treated cohorts suggest that ART is insufficient to reconstitute either the frequency or function of the γδ T‐cell subset. Recent advances are now beginning to shed light on the relationship between microbial translocation, chronic inflammation, immune ageing and γδ T‐cell immunology. Here, we review the impact of acute, chronic untreated and treated HIV infection on circulating and mucosal γδ T‐cell subsets and highlight novel approaches to harness γδ T cells as components of anti‐HIV immunotherapy. Abstract : In this review, we discuss the impact of HIV infection on circulating γδ T‐cell subsets and their antimicrobial function. We highlight current work focusing on the link between chronic inflammation, gut dysbiosis and γδ T‐cell trafficking. Finally, we explore the potential role for γδ T cells as components of anti‐HIV immunotherapy.